THE PERSPECTIVES OF SAME-SEX PARENTING IN SERBIA: BETWEEN NEEDS AND OPPORTUNITIES - Vlašković, Veljko; Arsić, Jelena - (Pravni zapisi, 2022)
In the context of current aspirations in terms of drafting and adopting a regulation that would finally legalize same-sex unions in Serbia, particularly important issue relates to the effect of same-sex union on the legal position of a child in such unity. The recently published text of the Draft Law on Same-Sex Unions undoubtedly opens the space for considering certain solutions related to the rights and obligations of a same-sex partner of a parent of the child, which is of direct importance in terms of exercising rights of the child in family relations. Based on these provisions, the authors seek to analyze legal possibilities and restrictions regarding the regulation of parental duties and rights of the child in the context of same-sex unions in Serbia. In these efforts, the authors commence from the relevant legal framework that regulates family relations, and thereby indicate some possible solutions.